Mitral and Aortic Regurgitation in Patients Undergoing Kidney Transplantation: The Natural Course and Factors Associated With Progression - Kim, Minjeong; Kim, Darae; Lee, Juhan; Kim, Dae-Young; Seo, Jiwon; Cho, Iksung; Huh, Kyu Ha; Hong, Geu-Ru; Ha, Jong-Won; Shim, Chi Young (Frontiers in Cardiovascular Medicine, 2022)
Background Valve regurgitation can decrease with resolution of hemodynamic loads on the left ventricle (LV) after kidney transplantation (KT). We aimed to investigate the natural course of left-side valve regurgitation after KT and factors associated with progression. Methods Among patients who underwent KT in two tertiary centers, 430 (224 men, mean age 50 ± 13 years) were examined by echocardiography within 3 months before KT and between 6 and 36 months after KT. Mitral regurgitation (MR) and aortic regurgitation (AR) were graded according to the current guidelines. Regression was defined as a decrease in regurgitation by one or more steps, and progression was an increase in one or more steps after KT. Clinical and echocardiographic factors associated with progression of MR and AR were analyzed. Results Mild or greater MR was observed in 216 (50%) patients before KT, and mild or greater AR was observed in 99 (23%). During the follow-up period of 23.4 ± 9.9 months, most patients experienced regression or no change in regurgitation after KT, but 34 patients (7.9%) showed MR progression and 37 (8.6%) revealed AR progression. Patients who showed MR progression were more likely to receive a second KT, have mitral annular calcifications, and show a smaller decrease in LV end-systolic dimension. Patients who showed AR progression were more likely to have persistent hypertension after KT, aortic valve calcifications, and a smaller reduction of LV end-systolic dimension. Conclusions Risk factors for progression of MR after KT include a second KT, MAC and a smaller decrease in LV end-systolic dimension after KT. Risk factors for progression of AR include valve calcification, persistent hypertension and a smaller decrease in LV end-systolic dimension after KT. Further echocardiographic surveillance and risk factor management after KT are warranted in these patients.